(3LhGgQ GdeYGfj aj efGbH GdTjN YHOGdbGOQ GdLjdGfjs - (3eMeO Hf YHO GdbGOQ GdJSJhGFjs ((3eMeO GdCeZGQj s)
(3ChdgG (B:s
(3CeG HYO , aEfg deG VGb GdUOQ JPGcQfj GddY HEMSGfg aYedJ acQi aj bUjOJg eSJYPHI s
(3BNQgG (B:s
(3Ke CNHQ Cf YOO CTjGNgG (B[(3Cj GdbUjOI(B] (3JbY JGA HKfJjf ef ahbgG, hgj CQHYeGFI JRjO bdjdkG s
(3hgh TQM dbUjOJg aj HjGf eMGSf GdChdjGA GdPjf EYJQahG HaVd GdTjN YHOGdbGOQ haj HjGf efGbHgs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs